Plasmodium falciparumvar Gene Is Activated by Its Antisense Long Noncoding RNA - Jing, Qingqing; Cao, Long; Zhang, Liangliang; Cheng, Xiu; Gilbert, Nicolas; Dai, Xueyu; Sun, Maoxin; Liang, Shaohui; Jiang, Lubin (Frontiers in Microbiology, 2018)
Plasmodium falciparum erythrocyte membrane protein 1, encoded by var gene, is an immunodominant antigen mediating immune evasion in humans. At a given time, only a single var gene is commonly expressed in one parasite. However, the regulation mechanism of var transcription remains largely unknown. In this study, we identified the antisense long non-coding RNA (aslncRNA) derived from var intron as an activation factor for the corresponding var gene. The exogenous artificial var aslncRNA transcribed by T7 RNA polymerase from episome can specifically activate the homologous var gene, and the exogenous aslncRNA activates transcription of both var mRNA and endogenous aslncRNA in a manner independent of the conserved intron sequence within the var gene family. Interestingly, the newly activated var gene and the previously dominant var gene then could be co-expressed in the same parasite nuclei, which suggests that the aslncRNA-mediated var gene activation could escape from the control of mutually exclusively expression of the var gene family. Together, our work shows that var aslncRNA is the activator responsible for var gene transcriptional regulation.